Atlas of adult physical diagnosis - Berg, Dale (Lippincott Williams & Wilkins, 2006)
This thoroughly illustrated text/atlas is the most comprehensive guide to physical examination techniques and physical diagnosis. Coverage of each anatomic site includes a review of anatomy, a general screening examination, and specific problem-oriented examinations, plus Teaching Points for physicians who precept medical students. A variety of techniques for each site and problem are shown, so that readers can adapt the examination to the patient. More than 700 illustrations (139 in full color) depict anatomic details, examination techniques, and significant findings. Tables present the evidence basis for various techniques. Annotated bibliographies are also included.